Geographic Extent of Flash Droughts Across the Seven Climatic Sub-regions of Vietnam - Thanh Ha, Pham; Van Tan, Phan (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1SDO - 10.25073/2588-1094/vnuees.5394, 2025)
This study analyzed the spatio-temporal characteristics of flash droughts across seven climatic sub-regions of Vietnam using ERA5 soil moisture data at three depths (7 cm, 28 cm, and 100 cm) over the period 1961 - 2020. The results reveal notable differences in flash drought occurrence between regions and across soil depths, with the shallowest layer (D7) showing the highest sensitivity to dry conditions. Although variations exist in absolute values, all results from three criteria consistently identify high flash drought frequency and duration in regions R1, R2, R4, and R7. Flash droughts primarily occur during the rainy season: JJA (June - August) in the northern regions (R1 - R3) and SON (September - November) in the southern regions (R4 - R7). Notably, flash droughts tend to occur on a broad spatial scale in sub-regions R1 - R3 and R7, where approximately 60% of the identified events affected more than 50% of the regional area, based on D7 and D28 criteria. These findings provide a scientific basis for selecting relevant variables and constructing appropriate input datasets for future flash drought forecasting and early warning models.